PREVENT ANEMIA BY CONSUMING BLOOD SUPPLEMENT TABLETS (FE) IN JUNIOR HIGH SCHOOL STUDENTS 11 AMBON GRADE 7 - Lapodi, Abd Rijali; Ibrahim , Rara Sabila; Pauwah , Rohdia (Jurnal Abdisci, 2024)
Until now, the prevalence of anemia in adolescent girls is still high; in 2024, Anemia in Indonesia will increase by 32% of adolescents aged 15-24 years in Indonesia experience anemia (Ministry of Health, 2024). The purpose of this socialization activity is to increase the knowledge of adolescent girls in preventing anemia. Prevention of anemia by administering blood-boosting tablets (Fe). The activity method consists of two, namely, planning and implementation. Planning includes coordination with the school and material preparation. The implementation is carried out face-to-face directly. The partners of this activity are young women at SMP Negeri 11 Ambon. This activity is carried out in education through various methods, namely lectures and the distribution of printed PowerPoint presentations (Handout). The activity will be held face-to-face on August 5, 2024. 14 young women attended. Education goes smoothly and can increase the knowledge of adolescent girls in preventing anemia. This activity received support from the Amahusu Health Center.